Effect of Cyprodinil and Fludioxonil Pesticides on Human Superoxide Dismutase - Karadag, H.; Bilgin, R. (Asian Journal of Chemistry, 2010)
Copper-zinc superoxide dismutase (CuZnSOD), (E.C:1.15.1.1) catalyzes the dismutation of the superoxide radical to hydrogen peroxide and oxygen. In this study, CuZnSOD was purified from human erythrocytes by DEAE-cellulose chromatography and copper-iminodiacetic acid agarose chromatography by 196.3 fold and 33.8 % efficiency. Specific activity of CuZnSOD was measured in purified enzyme extract and human erythrocytes treated with and without varying concentrations of cyprodinil and fludioxonil. CuZnSOD activity in 500 ppm cyprodinil treated erythrocytes was about 68.7 % of the initial CuZnSOD activity of control. Whereas CuZnSOD activity of erythrocytes treated with 500 ppm fludioxonil was about 33.9 % of the initial activity CuZnSOD activity of control. In the case of purified CuZnSOD activity treated with 500 ppm cyprodinil was about 76.2 % of the initial purified CuZnSOD activity of control. In same way purified CuZnSOD activity treated with 500 ppm fludioxonil was about 40.7 % of the initial purified CuZnSOD activity of control. In short, fludioxonil according to cyprodinil more inhibited CuZnSOD. Cyprodinil inhibited CuZnSOD competitively and fludioxonil inhibited CuZnSOD non-competitively.